Parasite cross-transmission between the Iberian wolf and wild ungulate prey - Figueiredo, Ana Manuel Bastos (2021)
Parasitic diseases have become a scientific priority, since they can pose not only a threat to humans and domestic animals, but also to wildlife, especially when concerning endangered species. As an apex predator and classified has “Endangered” in Portugal, the Iberian wolf (Canis lupus signatus) has na important role in modeling trophic interactions, contributing to biodiversity maintenance and ecosystem functioning. However, its spotlight position in the food web may also have counterparts, namely contributing to disease spread. In Montesinho Natural Park (MNP), northeast Portugal, the Iberian wolf shares its habitat with three wild ungulate species: red deer (Cervus elaphus), roe deer (Capreolus capreolus) and wild boar (Sus scrofa). Considering this scenario, there is a potential risk of parasite cross-transmission between the Iberian wolf and wild ungulate species, and so, in order to acknowledged this potential risk, between September 2017 and August 2018, a total of 162 fresh faecal samples were collected from both Iberian wolf (n=50) and wild ungulates (n=112). Iberian wolf scats submitted to diet analysis have confirmed high predation upon wild ungulates (88%), where wild boar was the most consumed prey (32%), followed by red and roe deer (28%, both), with low livestock consumption (6%). Coprological analysis of wild ungulates and Iberian wolf samples, showed a high parasite prevalence among wild ungulates samples (78.6%), coupled with high parasite diversity (e.g. Muellerius sp., Trichostrongylidae, Strongylidae, Metastrongylus sp., Moniezia benedeni, Eimeria spp., Cystosisospora sp. and Balantidium coli), representing not only a health risk for livestock, but also a significant public health risk. On the other hand, the low parasite prevalence found on the Iberian wolf samples (15.5%), although being pathogenic to humans and other wild and domestic animals, does not represent a major threat to this Iberian wolf population. The molecular analysis of parasites enhancing a direct trophic transmission or an indirect one, including both wolf and wild ungulates as hosts during its development, confirmed the presence of Giardia duodenalis, Cryptosporidium ubiquitum and Blastocystis sp. in the analysed samples. This study highlighted the importance of performing cross-transmission studies, in order to understand the main sources of infection and the danger that can be posed to local populations, especially when they present an endangered conservation status, like the Iberian wolf. The implementation of surveillance and monitoring programs is mandatory, not only with host species as conservation targets, but also parasites, due to their role in the ecological and evolutionary processes.